Imobilidade intra-hospitalar como desfecho adverso na saúde do idoso hospitalizado - Da Cás, Daniela Alves (2021)
Introduction: The senior immobility constitutes one of the greatest geriatric syndromes, being responsible for causing adverse outcomes in seniors’ health. Among the outcomes, it is observed that it generates longer hospitalization time, hospitalizations and death. Among the environments with more concern regarding the immobility, it is the hospital environment, which due to its own characteristics as bed dispositions, less mobility, acquired comorbidities, and underlying diseases, increase the frequency of this syndrome. Objective: Evaluate the predictors of intrahospital immobility in seniors. Methods: It is a quantitative study, longitudinal, and descriptive constituted by a prospective cohort. This study is derived from a portion of the project named “Development of a hospitalized senior health care in HUSM” under CAAE “48212915.50000.5346”. The data collection occurred between the months of September 2015 and July 2016, at the Santa Maria’s University Hospital/RS (HUSM). It was included seniors that entered hospital emergency by varying causes and that accepted to participate the study. It was excluded the individuals who were not capable to answer the survey (by cognitive or communication deficit), or by not having a companion at the survey time to provide the necessary data. It was used as descriptive variables: age, sex, admission pathology, period of hospitalization, and complications (pneumonia, fallings, urinary tract infection, deep vein thrombosis, delirium, and urinary incontinence), and as variable of study the intra-hospital immobility, the Identification of Seniors At Risk, Confusion Assessment Method, Edmonton Frail Scale , and calf circumference measurement. The descriptive analysis was performed (frequency, mean and median), chi-squared test, Backward Wald multivariate logistic regression, and Kaplan-Meier survival curve, significant values were considered when p≤ 0,05 (SPSS 21.0). Results: Among the 397 evaluated individuals, it was observed a predominance in early seniors between 60 and 69 (39.7%), male (53.7%). It was observed that the age (p=0.007), fragility indicators (p=0.007), and delirium (p=0.001) during the hospitalization increased the seniors’ chance to have intra-hospital immobility. Conclusion: These data suggest that the intra-hospital immobility is associated with the age, admissions’ pathology, CC values, frail scores, senior risk index, and comorbidity presence and the predictive variables to immobility were the age, frail, and admission delirium indication. In conclusion, it is suggested to consider these in the implementation of prevent measures as for senior’s intra-hospital immobility.